Macrophage: Key player in the pathogenesis of autoimmune diseases - Yang, Shuang; Zhao, Ming; Jia, Sujie (Frontiers in Immunology, 2023)
The macrophage is an essential part of the innate immune system and also serves as the bridge between innate immunity and adaptive immune response. As the initiator and executor of the adaptive immune response, macrophage plays an important role in various physiological processes such as immune tolerance, fibrosis, inflammatory response, angiogenesis and phagocytosis of apoptotic cells. Consequently, macrophage dysfunction is a vital cause of the occurrence and development of autoimmune diseases. In this review, we mainly discuss the functions of macrophages in autoimmune diseases, especially in systemic lupus erythematosus (SLE), rheumatic arthritis (RA), systemic sclerosis (SSc) and type 1 diabetes (T1D), providing references for the treatment and prevention of autoimmune diseases.